The Role Of The Information Technology In The Enterprise Integration With Business Processes Management - Bentriou, Mohamed; Touahar, Mohamed Touhami (جامعة الوادي - University of Eloued, 2019)
The enterprise integration with Business Processes ManagementBPM is a complex activity which has a great impact on key stakeholders including staff and customers.BPM is more important to have an integrated information systems that cut across various organizations as well as various functional areas. The aim o this paper is to present a developed view may be useful for recognising the concepts which may help to clarify the role of the BPM and the BPM systems in enterprise integration. They also offer a motivated method to understand and solve the problematic of BPM and BPM systems and their instruments for incorporating a company's specific functional features to assure the enterprise integration . This study concluded that the using of BPM to develop the company Processes lead to make the good integration and the good orientation of the efforts.However, the BPM solution can support the other IT tools to have a good integration
مقال
Keywords: Business Processes Management BPM ; Information System IS ; Information Technology IT ; Enterprise integration